A historical dictionary of psychiatry - Shorter, Edward (Oxford University Press, 2005)
This is the first historical dictionary of psychiatry. It covers the subject from autism to Vienna, and includes the key concepts, individuals, places, and institutions that have shaped the evolution of psychiatry and the neurosciences. An introduction puts broad trends and international differences in context, with an extensive bibliography for further reading. Each entry gives the main dates, themes, and personalities involved in the unfolding of the topic. Longer entries describe the evolution of such subjects as depression, schizophrenia, and psychotherapy. The book gives ready reference to when things happened in psychiatry, how and where they happened, and who made the main contributions. In addition, it touches on such social themes as "women in psychiatry," "criminality and psychiatry," and "homosexuality and psychiatry." A comprehensive index makes immediately accessible subjects that do not appear in the alphabetical listing. Bringing together information from the English, French, German, Italian, and Scandinavian languages, the dictionary rests on an enormous base of primary sources that cover the growth of psychiatry through all of Western society.